Extrusion of barley and oat influence the fecal microbiota and SCFA profile of growing pigs. Issue 2 (13th January 2016) - Moen, Birgitte; Berget, Ingunn; Rud, Ida; Hole, Anastasia S.; Kjos, Nils Petter; Sahlstrøm, Stefan
Abstract : The effect of extrusion of barley and oat on the fecal microbiota and the formation of SCFA was evaluated using growing pigs as model system. The pigs were fed a diet containing either whole grain barley (BU), oat groat (OU), or their respective extruded samples (BE and OE). Abstract : The effect of extrusion of barley and oat on the fecal microbiota and the formation of SCFA was evaluated using growing pigs as model system. The pigs were fed a diet containing either whole grain barley (BU), oat groat (OU), or their respective extruded samples (BE and OE). 454 pyrosequencing showed that the fecal microbiota of growing pigs was affected by both extrusion and grain type. Extruded grain resulted in lower bacterial diversity and enrichment in operational taxonomic units (OTUs) affiliated with members of the Streptococcus, Blautia and Bulleidia genera, while untreated grain showed enrichment in OTUs affiliated with members of the Bifidobacterium and Lactobacillus genera, and the butyrate-producing bacteria Butyricicoccus, Roseburia, Coprococcus and Pseudobutyrivibrio . Untreated grain resulted in a significant increase of n -butyric, i-valeric and n -valeric acid, which correlated with an increase of Bifidobacterium and Lactobacillus . This is the first study showing that cereal extrusion affects the microbiota composition and diversity towards a state generally thought to be less beneficial for health, as well as less amounts of beneficial butyric acid.